Orthopedic physical assessment - Magee, David J.; Manske, Robert C. (St. Louis, Missouri : Elsevier, 2021)
"Orthopedic Physical Assessment, 7th Edition covers the principles of assessment for all of the body's structures and joints, including topics such as gait, posture, the head and face, amputees, primary care, and sports emergencies. The Student Consult ebook version includes all of the photos and drawings from the print book plus additional functional assessment forms (e-tools), updated evidence-based reliability and validity tables, and hundreds of video clips demonstrating special tests on how to perform musculoskeletal assessment. Written by noted PT educators David J. Magee and Robert C. Manske, this reference uses a systematic, evidence-based approach to prepare you for success in clinicals, board exams, and in rehabilitation practice." --Provided by publisher.
Principles and concepts -- Head and face -- Cervical spine -- Temporomandibular joint -- Shoulder -- Elbow -- Forearm, wrist, and hand -- Thoracic (dorsal) spine -- Lumbar spine -- Pelvis -- Hip -- Knee -- Lower leg, ankle, and foot -- Assessment of gait -- Assessment of posture -- Assessment of the amputee -- Primary care assessment -- Emergency sports assessment.
Previous edition 2014 (6th ed.).
Includes bibliographical referencs and index.
Keywords: Musculoskeletal system -- Diagnosis; Orthopedics -- Diagnosis; Physical diagnosis; Physical orthopedic tests; tuki- ja liikuntaelimet; diagnostiikka; fysioterapia; motoriikka; nivelet; ortopedia; ryhti; tutkimus; kävely; luuston sairaudet; tuki- ja liikuntaelinten taudit